Financial Technology dan Customer Relationship Management dalam Meningkatkan Loyalitas Pelanggan - Suradi (Business Perspective Journal, 2025)
The rapid development of science and technology in today's digital era has influenced human behavior patterns in accessing diverse information and various electronic service features. One technological development currently under study in Indonesia is Financial Technology (FinTech). The purpose of this study is to determine 1) the influence of fintech on Customer Relationship Management, 2) the influence of Customer Relationship Management on Customer Loyalty, and 3) the influence of Customer Relationship Management on Customer Loyalty. This research method is library research, which is conducted using literature in the form of research books, journals, and previous research findings. The results of the literature review concluded that fintech influences Customer Relationship Management, CRM influences Customer Loyalty, and fintech influences Customer Loyalty. Keywords: fintech, Customer Relationship Management, Customer Loyalty